Evaluation of the Pharmacokinetics of Two Recombinant Human Erythropoietin Preparations: Epoetin Zeta and Epoetin Alfa - Kirkov, Valentin; Dimitrova, Velislava; Siebert-Weigel, Marianne; Wolf-Pflugmann, Michael; Koytchev, Rossen; Richter, Wolfram; Bronn, Angelika; Arsova, Sacha; Kromminga, Arno (Arzneimittelforschung, 2008)
The subcutaneous bioavailability of a new recombinant erythropoietin preparation (epoetin zeta, CAS 604802-70-2) and the pharmacokinetic properties of this drug compared to a reference product (epoetin alfa, CAS 113427-24-0) were analyzed after a single intravenous bolus injection or subcutaneous injection of 10,000 IU in a three-period crossover design in 48 healthy volunteers. Peripheral venous blood samples were obtained pre-dose, and 0:05, 0:20, 0:40, 1:00, 1:20, 1:40, 2:00, 3:00, 4:00, 6:00, 8:00, 12:00, 24:00, 36:00, 48:00, and 72:00 h post dosing. Samples from 48 volunteers were analyzed by means of a specific immunoassay (ELISA).The systemic bioavailability of epoetin zeta after subcutaneous administration is approximately 24 %. Comparison of both preparations showed nearly identical pharmacokinetic properties after subcutaneous administration. The usual bioequivalence limits were fulfilled for all relevant pharmacokinetic parameters.
Keywords: CAS 113427-24-0; CAS 604802-70-2; Epoetin alfa, bioavailability, bioequivalence, biosimilar, pharmacokinetics; Epoetin zeta, bioavailability, bioequivalence, biosimilar, pharmacokinetics